2020
DOI: 10.1108/jeee-02-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Bricolage as a path towards organizational innovativeness in times of market and technological turbulence

Abstract: Purpose Companies need guidance on how to operate in turbulent environments to improve their innovative performance. However, few studies have been done specifically about how to market and technological turbulence affects the innovative performance in emerging markets. This paper aims to propose model with market turbulence, technological turbulence and firm’s bricolage behavior as antecedents of organizational innovativeness. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
(133 reference statements)
1
29
0
Order By: Relevance
“…Obviously, the link between operational sustainability and firm performance is affected by the technology turbulence (TT), which impedes a firm's technological advancement. This concept is in consonance with other studies [37,38], according to which firms cannot ignore the technological turbulence and must respond promptly to market changes. Now, the effects of the moderator TT on the linkage H4 will be discussed and illustrated with graphs, as shown in Figure 3.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Obviously, the link between operational sustainability and firm performance is affected by the technology turbulence (TT), which impedes a firm's technological advancement. This concept is in consonance with other studies [37,38], according to which firms cannot ignore the technological turbulence and must respond promptly to market changes. Now, the effects of the moderator TT on the linkage H4 will be discussed and illustrated with graphs, as shown in Figure 3.…”
Section: Discussionsupporting
confidence: 85%
“…However, the rapid development of technology invites the menace of technology turbulence, which impedes firms from exhibiting better performance even after they achieve better operational sustainability [35,36]. Therefore, technology turbulence also needs to be addressed to ensure effective firm performance [37,38].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…CA could be sustained for a long time when a firm has a manpower that is difficult to be imitated or replaced by its rivals in the industry. The absence of abundant resources at the disposal of many firms clearly hampers their ability to innovate or engage in OI (Santos et al , 2020). The theory places emphasis on developing distinctive, inimitable and unsubstitutable resources as well as a dynamic way to integrate those resources to yield SCA and performance for SMEs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As mentioned above, the approach of an entrepreneur to customers is based on both his/her idea of the form of the company and market conditions, where growing competition creates pressure to apply new approaches. Rapid radical changes and an overall turbulent environment can play an important role here (Doern et al, 2019;Ratten, 2020;Santos et al, 2020), as shown in the past. For example, by the impact of oil shocks on the usage of cars in a short-term view (Sachs, 2008) or even on the preferences of customers that made the producers introduce passenger cars with lower fuel consumption in a long-term perspective (Mogridge, 1978).…”
Section: Covid-19 Crisis and Market Environmentmentioning
confidence: 73%